Shifts in chemical and microbiological properties belowground of invader Ageratina adenophora along an altitudinal gradient. (11th January 2022) - Li, Wei-Tao; Zheng, Yu-Long; Wang, Rui-Fang; Wang, Zheng-Ying; Liu, Yan-Mei; Shi, Xiong; Liao, Zhi-Yong; Li, Yang-Ping; Feng, Yu-Long
Abstract: Tropical mountain ecosystems are usually colonized by numerous invasive plant species and represent an ideal 'natural laboratory' to study the effects of altitude on plant invasion. The aim of this study was to investigate the soil chemical and microbiological properties along an altitudinal gradient on a mountain colonized by the invader Ageratina adenophora . Rhizosphere soil of A. adenophora was collected over an altitudinal gradient (1400–2400 m) in Ailao Shan, China. We determined soil organic carbon (C), nutrient contents, enzyme activities, bacterial community composition as well as C and nitrogen (N) contents of the plant roots. Ecoenzymatic stoichiometric indices were calculated to estimate the relative C, N or P limitations of the microbial community. There was a significant effect of altitude on soil organic C in the rhizosphere, and a turning point in these measured variables was detected at an altitude of 2000 m. At low elevations, the rapid growth of invasive plants depleted the deficient phosphorus (P) in tropical soils, leading to microbial P limitation; at high elevations, microbes invested more energy to obtain C from resistant litter, leading to microbial C limitation. Bacterial beta diversity and soil pH contributed most to the altitudinal differences in ecoenzymatic stoichiometry, and Proteobacteria and Acidobacteria were the dominant bacterial phyla that determined the nutrient uptake status of microorganisms. These results demonstrate how microbial nutrient acquisition belowground of A. adenophora along an altitudinal gradient, which could contribute to further knowledge about the effects of altitude on biological invasion.